Interaction Between Spiritual Development and Psychological Growth: Implications for Islamic Educational Psychology in Islamic Students - Syafii, Muhammad Hisyam; Azhari, Husain (Journal of Islamic Education and Ethics, 2025)
This study investigates the interaction between spiritual development and psychological growth among 72 Muslim university students, with implications for Islamic educational psychology. Spiritual development, centered on concepts such as taqwa (awareness of Allah) and tafaqquh fi al-din (deep religious understanding), is analyzed alongside psychological growth, encompassing cognitive, emotional, and behavioral aspects. Utilizing a mixed-methods approach, the study conducted quantitative analysis through Structural Equation Modeling (SEM) and qualitative analysis of reflective journals. The findings reveal that spiritual development is significantly correlated with psychological well-being (r = 0.64, p < 0.01), religiosity (r = 0.71, p < 0.01), and academic performance (r = 0.42, p < 0.01). Psychological well-being mediates the relationship between spiritual development and academic performance. The SEM model shows strong fit indices, with CFI and TLI values ​​above 0.90 and RMSEA below 0.06. The novelty of this research lies in integrating Islamic spiritual concepts such as tazkiyah al-nafs (soul purification) with modern psychological theories, providing a comprehensive framework for the spiritual-psychological development of Muslim students. Recommendations include incorporating these findings into Islamic education by developing holistic curricula, improving Islamic guidance and counseling, and enhancing educator competencies. Future studies should explore larger samples and longitudinal designs to investigate these relationships further.